A rare case of sigmoid colon cancer in which the lower limbs received collateral blood flow from the inferior mesenteric artery owing to peripheral artery disease - Kyoichi Kihara; Hiromu Horie; Kozo Miyatani; Masayuki Endo; Tomoyuki Matsunaga; Manabu Yamamoto; Shinsaku Yata; Naruo Tokuyasu; Teruhisa Sakamoto; Yoshiyuki Fujiwara (Surgical Case Reports)
Abstract Background Colorectal cancer and peripheral artery disease are common conditions in older adults and may coexist in this population. Lymph node dissection along the inferior mesenteric artery is a vital procedure in cases of left-sided colorectal cancer. However, the inferior mesenteric artery may show a collateral blood pathway in rare cases of peripheral artery disease. We report a case of advanced sigmoid colon cancer in which the lower limbs received inferior mesenteric artery flow owing to asymptomatic peripheral artery disease. The possibility of catastrophic lower-limb ischemia because of complete mesenteric excision with ligation of the inferior mesenteric artery was a matter of concern in this case. Case presentation A 73-year-old man with asymptomatic peripheral artery disease was diagnosed with stage IIIB advanced sigmoid colon cancer. Angiography using a balloon-occlusion catheter revealed that his lower limbs received prominent inferior mesenteric artery blood flow through a collateral pathway. Therefore, interventional radiologists and cardiovascular surgeons evaluated the indications for endovascular stents or bypass grafts. The patient also had dilated cardiomyopathy, so the cardiovascular physicians evaluated his tolerance in the worst-case scenario of a colorectal anastomotic leak. The patient underwent axillofemoral artery bypass and two-stage laparoscopic sigmoid colectomy without anastomosis. The postoperative course was uneventful, and he resumed his job within a month after the resection. Conclusions Although collateral flow from the inferior mesenteric artery is rare in patients with peripheral artery disease, a few case reports have described fatal lower-limb ischemia following anterior resection. The perioperative multidisciplinary evaluation enabled us to understand the patient’s condition and risks, and allowed successful cancer treatment without ischemia of the lower limbs.